How 5G will be different - Corner, Stuart (Journal of Telecommunications and the Digital Economy, 2014)
Mobile telecommunication services incorrectly branded ‘4G’ are now widely available. By contrast future mobile technology, dubbed 5G, has already received coverage in the mainstream press, but does not yet exist. This article summarises the ‘state of play’ in 5G by reviewing the requirements that are driving its development, the performance targets it is aiming for and the technologies being explored to achieve these. It will also examine the major collaboration initiatives that have been created to progress development towards universally accepted standards. Finally, it looks at what 5G services are expected to offer from the users’ perspective.